Peran Kepuasan Kerja sebagai Variabel Mediasi Pengaruh Budaya Organisasi terhadap Kinerja Karyawan - Abd Qomar (Fakultas Ekonomi dan Bisnis Islam, 2019)
The purpose of this research is to explain the influence of organizational culture on job satisfaction, the influence of organizational culture on employee performance, the effect of job satisfaction on employee performance and the role of job satisfaction as a mediating variable influence organizational culture on employee performance. This type of research is qualitative research that uses literature studies, in which it examines the influence between variables based on existing theoretical theories and is reinforced by empirical studies of relevant journal journals. The results of this study indicate that organizational culture has a positive effect on job satisfaction, organizational culture has a positive effect on employee performance, job satisfaction has a positive effect on employee performance and organizational culture has a positive effect on employee performance through job satisfaction.